Genotypic spectrum of α-thalassemia and β-thalassemia in newborns of the Li minority in Hainan province, China - Zhong, Kun; Shi, Haijie; Wu, Wenli; Xu, Haizhu; Wang, Hui; Zhao, Zhendong (Frontiers in Pediatrics, 2023)
Purpose To explore the genotypes and allele frequencies of α, β and α+β thalassemias in Li minorities, which resided in Hainan Province of China for a long time. Methods In the present study, 1,438 newborns of the Li minority were collected from January 2020 to April 2021. The genotypes of thalassemia were detected by fluorescence PCR and verified by flow-through hybridization PCR analyses. Rare genotypes were detected by restriction fragment length polymorphism electrophoresis and Sanger DNA sequencing. Results Among 1,438 participants, 1,024 (71.2%) were diagnosed with any kind of thalassemia. Among all thalassemia carriers, 902 (88.09%) subjects were diagnosed with α-thalassemia, and 18 subtypes of α-thalassemia were detected, with the top three genotypes being −α4.2/αα (25.39%), −α3.7/αα (22.62%) and αWSα/αα (16.96%). Thirty-two (3.13%) patients were β-thalassemia carriers, and 6 types of β-thalassemia genotypes were detected. The top two genotypes were βCD41–42/βN (46.88%) and β−28/βN (18.75%). Additionally, 90 (8.79%) cases were α + β-thalassemia, and the top two genotypes were −α3.7/αα, βCD41–42/βN (30.00%) and −α4.2/αα, βCD41–42/βN (26.67%). Furthermore, two genotypes (−α4.2/HKαα and βCD76 GCT > CCT/βN) were first identified in Hainan Province, and βCD76 GCT > CCT/βN was first identified in China. Conclusion Newborns of Li have a higher prevalence of thalassemia for a long period, and further education on the impact of thalassemia, follow-up studies of the clinical manifestation and treatment and proper intervention methods should be designed to reduce the burden of thalassemia and enhance the quality of life in Li newborns.